Main occurrences in the ophthalmological emergency with a focus on ocular trauma: an integrative review (Research, Society and Development, 2023)
Introduction: Ocular trauma is much more frequent in the emergency room than it seems, as it is an area of ​​high        sensitivity and a high probability of permanent and irreversible damage, a deeper study of the main diagnoses that occur in the emergency room is necessary. Objective: To analyze the ocular traumas that enter the ophthalmological emergency. Methodology: This study is an integrative literature review. The databases of scientific articles were used to perform the searches: US National Library of Medicine (PubMed) and Scientific Electronic Library Online (SciELO) Latin American and Caribbean Literature in Health Sciences (LILACS) and Biblioteca Virtual em Saúde (BVS) of scientific data up to December 20, 2022, in English, Portuguese and Spanish. The articles used are from the period from 2000 to 2022. The keywords “emergency” AND “ophthalmology” were used. Result and discussion: Emergency care in ophthalmology has always proved to be a challenge in medical practice, as it is an area little studied during After graduation, many professionals are insecure when carrying out procedures, which can lead to irreversible ocular damage.